COVID vaccination can be performed in patients with a history of allergic reactions to the vaccines or their components: experience from a specialist clinic in South Australia. Issue 11 (30th July 2022) - Tunbridge, Matthew; Perkins, Griffith; Lee, Maverick; Salehi, Tania; Ryoo, Dongjae; Kette, Frank; Smith, William; Gold, Michael; Le, Thanh‐Thao Adriana; Yuson, Chino; Hissaria, Pravin
Abstract: Background: The development of vaccines against SARS‐CoV2 has been a key public health response to the COVID‐19 pandemic. However, since their introduction, there have been reports of anaphylactic reactions to vaccines in individuals with history of allergic reactions to other vaccines, excipients or to COVID vaccines. Aim: A dedicated adult COVID vaccine allergy clinic with a standardised allergy testing protocol was set up to investigate safety and suitability of available COVID vaccines in Australia. Methods: Patients referred to a state‐wide COVID‐19 vaccine allergy clinic between March and August 2021 with a history of allergy underwent skin‐prick testing and intradermal testing to both available vaccine formulations (BNT162b2 and ChAdOx1‐S), excipients (polyethylene glycol and polysorbate 80), excipient‐containing medications and controls. Basophil activation testing was conducted in few subjects with convincing history of immediate type reactions. Results: Fifty‐three patients underwent testing for possible excipient allergy ( n = 19), previous non–COVID vaccine reaction ( n = 13) or previous reaction to dose 1 of COVID‐19 vaccine ( n = 21). Patients were predominantly female ( n = 43, 81%), aged 18–83 (median 54) years. Forty‐four patients tested negative and 42 of these received at least their first dose of a COVID‐19 vaccine. Nine patients tested positive to excipients or excipient‐containing medication only ( n = 3), or vaccines ( n = 6). Five patients were positive to just BNT162b2, 3/5 have been vaccinated with ChAdOx1‐S. One who was skin test positive to both vaccines, but negative BAT to ChAdOx1‐S was successfully vaccinated with ChAdOx1‐S. Conclusion: Even in a high‐risk population, most patients can be vaccinated with available COVID‐19 vaccines. This paper reports local experiences using a combined allergy testing protocol with skin testing and BAT during the pandemic.